1998
DOI: 10.1086/314520
|View full text |Cite
|
Sign up to set email alerts
|

Unresponsive CD4+T Lymphocytes fromLeishmania chagasi–Infected Mice Increase Cytokine Production and Mediate Parasite Killing after Blockade of B7‐1/CTLA‐4 Molecular Pathway

Abstract: Infection of BALB/c mice with Leishmania chagasi results in progressive increase of parasite burden in spleen, in spite of extensive T cell activation in situ. Explanted splenic CD4+ T cells showed decreased proliferation to anti-CD3, compared with controls, and no response to L. chagasi recombinant antigen Lcr1. Blockade of the negative costimulatory receptor CTLA-4 restored responses to anti-CD3 and induced vigorous responses to Lcr1. Blockade of B7-1, but not B7-2, also enhanced T cell responsiveness. CTLA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
24
1
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 15 publications
0
24
1
2
Order By: Relevance
“…While anti-CTLA-4 treatment produces variable effects and can exacerbate cutaneous L. major infection (10,15), anti-CTLA-4 is active both prophylactically and therapeutically against visceral L. donovani infection (20). In vitro studies with L. chagasi, another agent of visceral leishmaniasis, also support the antileishmanial effect of MAb blockade of either T-cell-expressed CTLA-4 or its B7 ligands on APC (10,11).…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…While anti-CTLA-4 treatment produces variable effects and can exacerbate cutaneous L. major infection (10,15), anti-CTLA-4 is active both prophylactically and therapeutically against visceral L. donovani infection (20). In vitro studies with L. chagasi, another agent of visceral leishmaniasis, also support the antileishmanial effect of MAb blockade of either T-cell-expressed CTLA-4 or its B7 ligands on APC (10,11).…”
mentioning
confidence: 83%
“…An alternative strategy to therapeutically harness the same Th1 cell mechanism has focused on T-cell costimulation (7,11,19,20). Optimal T-cell activation, including induction of the antileishmanial Th1 response with secretion of IL-12, IL-2, and IFN-␥, requires second (costimulatory) signals likely delivered via interaction of surface molecules on T cells and antigenpresenting cells (APC) (7,11,19,20,39,41).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the negative costimulatory T-cell receptor CTLA-4 has been characterized as an important negative regulator of T-cell activation (Waterhouse et al 1995). We found that antibody-mediated blockade of either CTLA-4 or its ligand B7-1, restored otherwise suppressed T-cell responses, increased IFN-γ production, and promoted rapid killing of L. chagasi parasites within splenic Mφ (Gomes et al 1998). Although the mechanisms of CTLA-4 suppression of T-cell activation are still undefined, a recent study demonstrated that engagement of CTLA-4 promotes the production of TGF-β by CD4 + T cells, while inhibiting the production of all other cytokines tested (Chen et al 1998).…”
mentioning
confidence: 81%
“…In this disease, the splenic load of L. chagasi increases indefinitely, and local CD4 + T cells are unresponsive to mitogen or leishmanial antigen stimulation, but do not undergo AICD (Gomes et al 1998). Recently, the negative costimulatory T-cell receptor CTLA-4 has been characterized as an important negative regulator of T-cell activation (Waterhouse et al 1995).…”
mentioning
confidence: 99%